2006
DOI: 10.1111/j.1440-1843.2006.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar epithelial cells: differentiation and lung injury

Abstract: Alveolar epithelial cells: differentiation and lung injury SUGAHARA K, TOKUMINE J, TERUYA K, OSHIRO T. Respirology 2006; 11 : S28-S31 Abstract: Re-epithelialization of alveolar epithelial cells is one of the important repair processes in many types of lung injury. The major functions of alveolar type II cells are synthesis and secretion of surfactant, hyperplasia in reaction to alveolar epithelial injury, and serving as progenitor cells for alveolar type I cells. The authors have examined the effects of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 8 publications
1
23
0
1
Order By: Relevance
“…The conciliating concept to determine the outcome may be the balance between alveolar epithelial inflammation or vascular endothelial injuries and their repair mechanisms [39] (Table 1). …”
Section: Experimental Studiesmentioning
confidence: 99%
“…The conciliating concept to determine the outcome may be the balance between alveolar epithelial inflammation or vascular endothelial injuries and their repair mechanisms [39] (Table 1). …”
Section: Experimental Studiesmentioning
confidence: 99%
“…13) (28,30). It has been reported that fibroblasts isolated from IPF lungs have heterogenous phenotypes, suggesting that fibroblasts are derived from multiple cell types, including bone marrow and alveolar epithelial cells (13,24).…”
mentioning
confidence: 98%
“…Alveolar epithelial cells are critical for maintaining lung tissue homeostasis and are also important in host defense and innate immunity (Qian et al, 2006;Sugahara et al, 2006;Serrano-Mollar et al, 2007). We have recently demonstrated that disruption of Nrf2 leads to alveolar epithelial cell growth arrest accompanied by oxidative stress (diminished levels of GSH and increased levels of ROS; Reddy et al, 2007a), which is correlated with diminished mRNA expression levels of genes encoding Gclc and Gclm enzymes and dysregulation of networks of transcriptional programs involved in cell proliferation (Reddy et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%